Orthosiphon stamineus Leaf Extract Affects TNF-α and Seizures in a Zebrafish Model - Choo, Brandon Kar Meng; Kundap, Uday P.; Kumari, Yatinesh; Hue, Seow-Mun; Othman, Iekhsan; Shaikh, Mohd Farooq (Frontiers in Pharmacology, 2018)
Epileptic seizures result from abnormal brain activity and can affect motor, autonomic and sensory function; as well as, memory, cognition, behaviour or emotional state. Effective anti-epileptic drugs (AEDs) are available but have tolerability issues due to their side effects. The Malaysian herb Orthosiphon stamineus, is a traditional epilepsy remedy and possesses anti-inflammatory, anti-oxidant and free-radical scavenging abilities, all of which are known to protect against seizures. This experiment thus aimed to explore if an ethanolic leaf extract of Orthosiphon stamineus has the potential to be a novel symptomatic treatment for epileptic seizures in a zebrafish model; and the effects of the extract on the expression levels of several genes in the zebrafish brain which are associated with seizures. The results of this study indicate that Orthosiphon stamineus has the potential to be a novel symptomatic treatment for epileptic seizures as it is pharmacologically active against seizures in a zebrafish model. The anti-convulsive effect of this extract is also comparable to that of diazepam at higher doses and can surpass diazepam in certain cases. Treatment with the extract also counteracts the upregulation of NF-Kβ, NPY and TNF-α as a result of a Pentylenetetrazol (PTZ) treated seizure. The anti-convulsive action for this extract could be at least partially due to its downregulation of TNF-α. Future work could include the discovery of the active anti-convulsive compound, as well as determine if the extract does not cause cognitive impairment in zebrafish.